ENVIRONMENTAL ACCOUNTING OF COMPANIES IN CAMEROON - NGENGE , Martin Mbanda; NWAHANYE , Emmanuel; OUSMANOU , Alim (Revue Internationale des Sciences de Gestion, 2025)
The objective of this study is to examine the environmental accounting practices of Cameroonian companies. Secondary data were used from 40 companies in the manufacturing, agricultural, transport, and service sectors, which have sustainable development reports. An explanatory research design and descriptive statistics were used to assess the extent and variation of environmental accounting reporting, costs, and disclosures across sectors and company maturity. The study reveals that the majority of companies use quantitative environmental accounting and costs in accordance with current legislation, while environmental accounting disclosure is qualitative. Regarding company maturity, mature companies tend to provide more qualitative information, while less mature companies disclose higher levels of environmental information. The study recommends that, in addition to local regulatory practices, companies expand their business planning to include regulatory bodies to evolve social requirements and strengthen stakeholder interest, corporate image, and reputation. Furthermore, the Cameroonian government should create a legal framework to promote the development of environmental accounting practices among Cameroonian companies.